Comparison between measured and predicted path loss for mobile communication in Malaysia - Chebil, Jalel; Lawas , Ali K.; Islam, Md. Rafiqul (IDOSI Publication, 2013)
Path loss models are crucial in the planning of wireless network as they assist in interference estimations, frequency assignments and evaluation of cell parameters. This paper reports measurement results of the propagation path loss in four locations in the suburban area of Kuala Lumpur. The measured path loss at each location is extracted from the data and compared with the corresponding results obtained from the six models: Log-normal shadowing, Lee model, Stanford University Interim model (SUI), COST231 Hata model, Egli model and the Electronic Communication Committee (ECC)-33. The measured results show that the SUI and the log-normal models give in general a better prediction and can be used to estimate path loss for prediction of mobile coverage in a microcell in Malaysia. Egli model and the Electronic Communication Committee (ECC)-33. The measured results show that the SUI and the log-normal models give in general a better prediction and can be used to estimate path loss for prediction of mobile coverage in a microcell in Malaysia.